Uji Laboratorium Sampel Core Plug untuk Menentukan Porositas, Permeabilitas dan Saturasi Minyak pada Reservoir Batugamping - Arief Rahman; Rani Rahmawati (Publikasi Indonesia, 2022)
Porosity, permeability, and fluid saturation (gas, oil, water) are three important physical properties of rocks, especially in oil and gas reservoirs (oil and gas) which are carried out in core rock analysis. The purpose of this study is to determine the relationship between porosity, permeability, and oil saturation in limestone (limestone) from a horizontal plug core sample to a vertical core plug sample, to be associated with its distribution vertically and horizontally (laterally). The research method used is a Lab Test conducted at the Routine Core Analysis (RCAL) Laboratory at PPTMBG